EFFECT OF GELLING AGENTS ON COLOR CHARACTERISTICS OF FRUIT JAMS - & et al., Jancikova (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
This study was aimedto evaluate the influence of carrageenan and pectin on jam color during 10 days of cold storage (+ 4 ºC). Jam samples were prepared with cherry and apricot fruits and 3 concentrations of gelling agents (0.5 %, 1 % and 2 %). Cherry and apricot jam samples prepared without gelling agent were used as control samples. Pectin, κ-carrageenan and ι-carrageenan were used as gelling agents. The jams were stored in the refrigerator for 10 days. The color of jams was monitored by personal camera, with the usage of image analysis software in three intervals (first day, third day and tenth day). The significant (p<0.05) changes of color during 10 days of storage were measured in all prepared jam samples with emphasis that the lowest changes were observed in jams prepared with 1 % pectin, 0.5 % κ-carrageenan and 2 % ι-carrageenan. Otherwise, Principal component analysis (PCA) illustrated that only jam samples prepared with 1 % κ-carrageenan had different RGB parameters in comparison with other laboratory prepared jam samples.